PENGARUH LIKUIDITAS, RENTABILITAS, SOLVABILITAS, PERKEMBANGAN PERUSAHAAN, DAN KINERJA SAHAM TERHADAP RETURN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2006-2015 - B2091141037, GITA PUTRI MAULIDYA (MAKSI UNTAN, 2016)
This research on investment in the capital market aims to provide information and assessment to investors who will invest in a company. There are many factors that affect the movement of a stocks that brings profits for the investors. The factors examined include : liquidity, rentability, solvability, corporate development and stock performance on stock returns. The research was conducted on mining companies listed in the Indonesia Stock Exchange (IDX) in the periode from 2004 to 2015. This study used a multiple regression analysis with stock returns as the dependent variable and liquidity, rentability, solvability, corporate development and stock performance as the independent variables. The research carried out for 10 years took samples of 10 mining companies using purposive sampling. The result of this study showed that there was a significant effect of rentability (ROA), and stock performance (PER) on stock returns, while simultaneously the variables of liquidity, solvability and corporate development had no significant affect on stock returns. Keywords: stock returns, liquidity, rentability, solvability, corporate development, stock performance, mining companies, IDX.